Late-onset Anorectal Disease and Psychosocial Impact in Survivors of Childhood Cancer: A Report from the Childhood Cancer Survivor Study - Madenci, Arin L. (Cancer, 2019)
BACKGROUND: The prevalence and associated psychosocial morbidity of late-onset anorectal disease after surgery and radiotherapy for treatment of childhood cancer is not known. METHODS: A total of 25,530 survivors diagnosed between 1970–1999 (median age at cancer diagnosis, 6.1 years; age at survey, 30.2) and 5,036 siblings were evaluated for late-onset anorectal disease, defined as self-reported fistula-in-ano, self-reported anorectal stricture, or pathology- or medical record-confirmed anorectal subsequent malignant neoplasm (SMN) 5 or more years after primary cancer diagnosis. Piecewise exponential models compared the survivors and siblings and examined associations between cancer treatments and late-onset anorectal disease. Multiple logistic regression with generalized estimating equations evaluated associations between late-onset anorectal disease and emotional distress, as defined by the Brief Symptom Inventory-18 (BSI-18), and Health Related Quality of Life, using the 36-item Short Form Health Survey (SF-36). RESULTS: By 45 years after diagnosis, 394 survivors (fistula, n=291; stricture, n=116; anorectal SMN, n=26) and 84 siblings (fistula, n=73; stricture, n=23; anorectal neoplasm, n=1) developed late-onset anorectal disease (adjusted rate ratio [RR]=1.2 for survivors vs. siblings, 95% CI=1.0–1.5). Among survivors, pelvic radiotherapy ≥30 Gy within five years of cancer diagnosis was associated with late-onset anorectal disease (30–49.9 Gy vs. none, adjusted RR=1.6, 95% CI=1.1–2.3; ≥50 Gy vs. none, adjusted RR=5.4, 95% CI=3.1–9.2). Late-onset anorectal disease was associated with psychosocial impairment in all BSI-18 and SF-36 domains. CONCLUSIONS: Late-onset anorectal disease was more common among childhood cancer survivors who received higher doses of pelvic radiotherapy and was associated with substantial psychosocial morbidity.